2005
DOI: 10.1510/icvts.2004.101576
|View full text |Cite
|
Sign up to set email alerts
|

NT-proBNP in cardiac surgery: a new tool for the management of our patients?

Abstract: Preoperative NT-proBNP levels depend on preoperative patient status (Euroscore, NYHA class and cardiac rhythm) and they increase significantly after cardiac surgery. This increase is higher when postoperative inotropes are needed. We found no relation between NT-proBNP levels and complications rate. An association have been shown between NT-proBNP levels and the use of inotropes after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
5
14
0
2
Order By: Relevance
“…Here we found that there was no correlation between pre-operative or post-operative NT-proBNP and aortic cross-clamping time in CVR, which was similar to other results (15)(16)(17)(18), but it was different from the results of Berendes et al or Rafal et al (8,19). Their studies showed that BNP correlated with aortic cross-clamping time.…”
Section: Discussionsupporting
confidence: 78%
“…Here we found that there was no correlation between pre-operative or post-operative NT-proBNP and aortic cross-clamping time in CVR, which was similar to other results (15)(16)(17)(18), but it was different from the results of Berendes et al or Rafal et al (8,19). Their studies showed that BNP correlated with aortic cross-clamping time.…”
Section: Discussionsupporting
confidence: 78%
“…The levels of Nt-proBNP increased significantly compared to baseline levels from the first to the 4 th postoperative day with a peak at 2 nd day. Our results are consistent with those of Reyes et al [10] In this study, preoperative levels of Nt-proBNP (1371 ± 759.9 pg / ml with a median of 366 pg/ml) increased significantly after CPB surgery from postoperative day 1 to the 4 th postoperative day. In their study including 83 patients, no difference in the type of surgery was reported.…”
Section: Discussionsupporting
confidence: 93%
“…In their study including 83 patients, no difference in the type of surgery was reported. [10] The study of Berendes et al [11] also showed a significant increase in BNP levels after cardiac surgery. However, in their study, including 60 CABG and 43 VR patients, BNP levels were significantly increased in VR patients as compared to CABG ones.…”
Section: Discussionmentioning
confidence: 94%
“…The perioperative release pattern of copeptin in our study differs to natriuretic peptides. In uncomplicated cardiac surgery patients NT-proBNP raise until day 3-4 postoperatively and thereafter start to decline 25 . This difference in temporal release curves may illustrate the fact that NT-proBNP and copeptin are secreted as respons to different aspects of stress during heart surgery.…”
Section: Discussionmentioning
confidence: 99%